A one year retrospective study of gastroenteritis outbreaks in Croatia : incidences and etiology - Pajan-Lehpaner, Gordana (Array, 2009)
Abstract: Gastroenteritis is one of the most commonly reported communicable diseases in Croatia, where there is a well-established system for the surveillance of this disease. The aim of this study was to identify the frequency and the most causative agents of gastroenteritis outbreaks and to identify underlying factors contributing to disease outbreaks.We analysed 89 reported outbreaks documented by local epidemiologists to the Croatian National Institute of Public Health during 2006. Most outbreaks happened during the summer (39.3%).Causative agents in the summer were mostly bacteriae while viruses were mostly the causative agents in the spring (p<0.01). Also bacteria was the most causative agent in outbreaks conducted in private households and public restaurants, while viruses, mostly norovirus, were causative agents in outbreaks in homes for elderly people and hospitals (p<0.01). Bacterial infections were related to substandard practices in food preparation and warehousing, and virus infections were related to person-to-person contact (fecal-oral route and airborne transmission) (p<0.01). However, it is important to recognize the need for continuous public education, especially for professionals involved in food preparing as a step in how to prevent gastroenteritis